Single-Cell RNA Sequencing to Identify Natural Killer Cell-Linked Genetic Markers and Regulatory Biomolecules in Coronary Heart Disease - Apu, Prosenjit Saha; Hossain, Md. Arju; Shakil, Md.; Reza, Md. Selim; Ansari, Siddique Akber; Ansari, Irfan Aamer; Humayoo, Mahammad; Rahman, Md Habibur (Current Bioinformatics, 2025)
<span class=
Keywords: biomarkers